2014
DOI: 10.1093/rpd/ncu150
|View full text |Cite
|
Sign up to set email alerts
|

A report on radioactivity measurements of fish samples from the West Coast of Canada

Abstract: Even though many studies have shown that radioactive caesium levels in fish caught outside of Japan were below experimental detection limits of a few Bq kg−1, significant public concern has been expressed about the safety of consuming seafood from the Pacific Ocean following the Fukushima-Daiichi nuclear accident. To address the public concerns, samples of commonly consumed salmon and groundfish harvested from the Canadian west coast in 2013 were analysed for radioactive caesium. None of the fish samples analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
1
8
3
Order By: Relevance
“…Also, a study with an emphasis in understanding the impact of Fukushima nuclear plant incident on marine environment (West coast of Canada), indicated the presence of man-made isotopes of 134 Cs and 137 Cs in fish samples [10]. Another radioactivity study performed on various aquatic organisms within a confined waterbody (for Example Lake) indicated that the levels of radiation uptake in fish are dependent on aquatic habitation and food inclination [11].…”
Section: Introductionmentioning
confidence: 99%
“…Also, a study with an emphasis in understanding the impact of Fukushima nuclear plant incident on marine environment (West coast of Canada), indicated the presence of man-made isotopes of 134 Cs and 137 Cs in fish samples [10]. Another radioactivity study performed on various aquatic organisms within a confined waterbody (for Example Lake) indicated that the levels of radiation uptake in fish are dependent on aquatic habitation and food inclination [11].…”
Section: Introductionmentioning
confidence: 99%
“…The first was to provide clear and concise information regarding the potential for negative health impacts to the public associated with consuming Pacific salmon potentially contaminated with anthropogenic, e.g., Fukushima-derived radionuclides. Previous studies have attempted to measure the 134 Cs and 137 Cs content in Pacific salmon; 13,14 however, when attempting to measure individual samples, high detection limits have been a limiting factor. A more recent study 15 analysing sockeye salmon collected from Alberni Inlet on the west coast of Vancouver Island, BC, in June of 2014 did detect 137 Cs in five of the ten sockeye salmon sampled.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the low rate of gamma emission, 210 Po in each sample could not be measured with GEARS. For the dose calculation, the average 210 Po activity concentration in chum salmon collected from the Canadian west coast measured by Chen et al 13 was used in the dose calculation. To convert the activity concentrations in the salmon samples into effective doses received by individuals for the special case of consuming the salmon, dose coefficients from ICRP Publication 119 29 were used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations